2017
DOI: 10.1016/j.jhtm.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Precursors to the financial and strategic orientation of hotel property capital budgeting

Abstract: The purpose of this study is to develop and test a set of hypotheses concerned with exploring for precursors to the degree of emphasis hotel property General Managers attach to a financial versus strategic orientation in capital budgeting. Results are based on 200 survey responses from the General Managers of Australian and New Zealand hotels. The findings indicate that capital budgeting is more financially orientated than strategically oriented in hotel properties that adopt a management contract and also whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 109 publications
(110 reference statements)
0
4
0
4
Order By: Relevance
“…Nevertheless, challenges arise because in the real-world as capital expenditure decisions are complex (Bower, 1970;Bromiley, 1986;King, 1975;Marsh, Barwise, Thomas, & Wensley, 1988), messy, iterative and only partly rational (Braybrooke & Lindblom, 1963;Hickson, Butler, Cray, Mullory, & Wilson, 1986;King, 1975;Mintzberg, Raisinghani, & Thoeoret, 1976;Quinn, 1980). Within the context of hotel properties, several studies have also demonstrated considerable deficiencies in the capital expenditure decision-making process (e.g., Turner, 2017;Turner & Guilding, 2010a, 2010b, 2013.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, challenges arise because in the real-world as capital expenditure decisions are complex (Bower, 1970;Bromiley, 1986;King, 1975;Marsh, Barwise, Thomas, & Wensley, 1988), messy, iterative and only partly rational (Braybrooke & Lindblom, 1963;Hickson, Butler, Cray, Mullory, & Wilson, 1986;King, 1975;Mintzberg, Raisinghani, & Thoeoret, 1976;Quinn, 1980). Within the context of hotel properties, several studies have also demonstrated considerable deficiencies in the capital expenditure decision-making process (e.g., Turner, 2017;Turner & Guilding, 2010a, 2010b, 2013.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the three approaches to ownership and management are the owner-operator, franchise agreement and management contract (Gannon & Johnson, 1997). Owned-and-operated properties eliminate confounds due to agency problems that occur when contracting capital budgeting issues arise between owners and managers (Guilding, 2003; Turner, 2017; Turner & Guilding, 2010a, 2010b, 2012). In management contracted hotels, owners may involve themselves in the capital budgeting process, but their involvement is mitigated by the degree of power they hold in the owner-manager relationship (Turner & Guilding, 2013).…”
Section: Research Sitementioning
confidence: 99%
“…Pesquisas anteriores exploraram perfis e características gerais de gerentes de hotéis. Por exemplo, no Reino Unido Riley, 1996); nos EUA (Nebel;Ju-Soon;Vidakovic, 1995); na Grécia (Akrivos;Reklitis, 2007); na Croácia (Sehanovic et al, 2000); na Escócia (Harper;Brown;Wilson, 2005); na Coréia (Kim;Chun;Petrick, 2009); Austrália e Nova Ze-lândia (Turner, 2017). A presente pesquisa diferencia-se dos estudos anteriores ao explorar co-mo as características dos gestores de hotéis influenciam nas escolhas de práticas mais ou menos sofisticadas.…”
Section: Palabras Claveunclassified
“…Particularmente, no setor hoteleiro as decisões envolvendo o orçamento de capital são importantes. Pois o crescimento e a manutenção dos valores das pro-priedades, bem como os níveis mais elevados de satisfação e ocupação dos hóspedes, dependem em parte dessas decisões de investimento (Turner, 2017). Turner e Guilding (2010) observam que a administração de hotéis tende a ser liderança no que diz respeito ao início das propostas orçamentárias de capital.…”
unclassified
See 1 more Smart Citation